Exopolysaccharides from lactic acid bacteria: Structural analysis, molecular weight effect on immunomodulation - Surayot U. (Elsevier, 2014)
Exopolysaccharides (EPS) obtained from the culture medium of Lactobacillus confusus TISTR 1498 were investigated to determine their molecular characteristics and the effect of molecular weight (Mw) on immunomodulatory activity. The EPS mainly consisted of carbohydrates (81.9±2.4%) with only one type of monosaccharide, D-glucose, which was mostly connected by α-(1→6) glycosidic linkages. The EPS itself was unable to stimulate RAW264.7 cells to produce pro-inflammatory mediator nitric oxide (NO) and cytokines. However, considerable stimulation of RAW264.7 cells was observed by the low Mw of EPSs having Mw values≤70×103g/mol. The partially hydrolyzed EPS stimulated RAW264.7 cells to induce considerable NO and various cytokine production such as TNF-α, IL-1β, IL-6 and IL-10 via up-regulation of their mRNA expression. In addition, the degradation Iκ-B and the phosphorylation of c-Jun NH2-terminal kinase (JNK) were facilitated by BW-30 and MW-40, suggesting that the partially hydrolyzed EPS stimulated RAW264.7 cells through the activation of NF-κB and JNK pathways. © 2014 Elsevier B.V.